When Good Governance Isn’t Enough: Government Pressure as a Moderator of Greenwashing Behavior - Andy Iranda; Etna Nur Afri Yuyetta (Universitas Negeri Yogyakarta, 2026)
This study examines the effect of corporate governance on greenwashing and the moderating role of government pressure. Using panel data from 34 non-financial firms listed on the Indonesia Stock Exchange for 2017–2023, the results show that board gender diversity significantly reduces greenwashing, while board size and independence have no direct effect. Activist pressure strengthens the negative effect of board size on greenwashing, whereas government pressure enhances the impact of gender diversity and board independence. These findings indicate that effective governance combined with strong regulatory oversight can minimize symbolic sustainability disclosures. The study contributes to legitimacy theory by showing that governance effectiveness depends on external institutional forces. Practically, it suggests the importance of strengthening ESG regulations, third-party assurance, and substantive governance practices to promote corporate transparency and accountability.